From Basic Human Values to Interpersonal Violence: A Mental Illness Sample. Issue 3 (15th March 2020) - Rossi, Alessandro; Talevi, Dalila; Collazzoni, Alberto; Parnanzone, Serena; Stratta, Paolo; Rossi, Rodolfo
ABSTRACT: Personal values are motivational constructs which guide behavior. Associations between values and risky behaviors have been reported in student and non-clinical samples. We investigated the relationship between human values and variables related to interpersonal violence and maltreatment in a sample of 160 consecutively admitted people with mental disorders. The results found that human values related to openness to change and self-enhancement (i.e. Stimulation/Achievement) were positively correlated with interpersonal violence and maltreatment, while values related to conservation (i.e. Conformity/Tradition) were related to reported Support. This pattern of correlation was shared by people with psychosis and personality disorders but not by people with mood disorders. The results underlined the relations between human values and dysfunctional behaviors like interpersonal violence. This study suggests a need to consider a negotiation of human values when working on harm reduction models of treatment for those who are diagnosed with mental illness.